2007
DOI: 10.1111/j.1540-4609.2007.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Media Naturalness and Online Learning: Findings Supporting Both the Significant‐ and No‐Significant‐Difference Perspectives

Abstract: Is the use of an online course delivery format, when compared with the more traditional face-to-face format, good or bad in the context of university education? Those who subscribe to the no-significant-difference perspective argue that online delivery is good, because it allows students with time and geographic distance constraints to obtain the education that they need, with no significant negative impact on the quality of the learning experience. Others argue that online delivery is bad, advocating a versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 28 publications
(50 reference statements)
2
43
0
Order By: Relevance
“…Sacco and Ismail 2014). This is in accordance with Darwinian evolutionary principles, according to which face-to-face communication has evolved among mankind over thousands of years and includes a range of social communication cues, such as facial expressions, vocal intonation and body language (Kock 2005;Kock and Garza 2011;Kock, Verville, and Garza 2007). MNT suggests five criteria for assessing the level of media naturalness: (1) co-location in a common physical space, (2) a high level of synchronicity that enables immediate I.…”
Section: Literature Reviewmentioning
confidence: 79%
“…Sacco and Ismail 2014). This is in accordance with Darwinian evolutionary principles, according to which face-to-face communication has evolved among mankind over thousands of years and includes a range of social communication cues, such as facial expressions, vocal intonation and body language (Kock 2005;Kock and Garza 2011;Kock, Verville, and Garza 2007). MNT suggests five criteria for assessing the level of media naturalness: (1) co-location in a common physical space, (2) a high level of synchronicity that enables immediate I.…”
Section: Literature Reviewmentioning
confidence: 79%
“…However, the contingency table 6 shows that students in the face-toface sections (58.4%) outperformed those in the online sections (41.6%). In likeness to the findings of this study, the reviewed literature reveals a predominance of non significant differences found between the two modes of delivery (Carbonaro, et al, 2006;Hoban, et al, 2002;Kock et al, 2007;McFarland & Hamilton, 2005;Upton, 2006).…”
Section: Summary and Future Researchmentioning
confidence: 93%
“…A study conducted by Kock et al (2007) supports both the significant-and no-significantdifference perspectives after examining students' perceptions and grades at two points in time.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations